Differences in Electrochemically Deposited PEDOT(PSS) Films on Au and Pt Substrate Electrodes: A Quartz Crystal Microbalance Study. Issue 4 (29th December 2017) - Jarvis, Jennifer M.; Guzinski, Marcin; Perez, Felio; Pendley, Bradford D.; Lindner, Ernő
Abstract: Studying the responses of potassium ion‐selective electrodes with poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate), PEDOT(PSS), as solid contact (SC) revealed significant differences in the equilibration times and standard potentials of the electrodes fabricated on Au or Pt as substrate electrodes. To trace the source of these differences, PEDOT(PSS) films were deposited under the same conditions onto Au and Pt electrodes on the surface of 10 MHz quartz crystals. During the galvanostatic polymerization, the frequency decrease of the quartz crystal was monitored by an electrochemical quartz crystal microbalance (EQCM). In the initial 15 seconds of the electrochemical deposition, the rate of PEDOT(PSS) polymer growth was significantly faster on Au compared to Pt although the current density used for the deposition was the same. Consequently, the total frequency change after a given electrolysis time was always larger on Au compared to Pt, indicating a larger deposited mass or PEDOT(PSS) layer thickness. The differences in the thicknesses of the PEDOT(PSS) films on Au and Pt could be quantitatively confirmed by X‐ray photoelectron spectroscopy (XPS) etching studies. Scanning electron microscopy (SEM) analysis of PEDOT(PSS) films on Au and Pt also showed characteristic differences. Abstract :